تأثير بعض المؤشرات البيولوجية والوراثية للمطاعيم في نجاح تطعيم غراس الخرنوبCeratoniasiliqua L. وفي تطور نموها اللاحق - أمين, طلال; محفوض, حافظ; قازنجي, فادي (Latakia University Journal -Biological Sciences Series, 2017)
نفذ هذا البحث خلال موسم 2014 -2015 في مركز البحوث العلمية الزراعية.يهدف البحث إلى تحديد أثر بعض المؤشرات البيولوجية والوراثية على نجاح تطعيم غراس الخرنوب بالمشتل بدراسة ثلاثة أنماط من التطعيم: الذاتي والمتشابه والمتباين. استخدمت أصول بذرية بعمر سنة من طرازين وراثيين منتخبين في صنوبر جبلة والحفة, أخذت المطاعيم من غراس بعمر سنة نتجت من هذين الطرازين أو من فروع بعمر سنة منهما أيضاً ونفذ التطعيم بالقلم بطريقة التطعيم اللساني في فصل الربيع. أظهر التطعيم الذاتي أثر العوامل البيولوجية والوراثية للمطاعيم على نجاح التطعيم, حيث تفوق التطعيم الذاتي على المتباين بدلالة معنوية لكلا الطرازين الوراثيين سواء كان الطعم فتياً أم معمراً. وتفوق التطعيم الذاتي معنوياً على الأنماط الأخرى من حيث تطور المطاعيم. كما وجد تباين في قيم المؤشرات البيولوجية بين الطرازين المدروسين, لصالح طراز صنوبر جبلة على طراز الحفة بشكل غير معنوي. بالنسبة لعمر المطاعيم, تفوقت قيم التطعيم المتباين بالطعوم الفتية معنوياً على التطعيم المتباين بالطعوم المعمرة من حيث نسبة نجاحالتطعيم وقيم المؤشرات البيولوجية المدروسة. This research was carried out during 2014 - 2015 in Scientific Centre for Agricultural Researches. This research aims to determine the effect of some biological and genetic indicators on the success of Carob seedlings in nurseries by studying three kinds of grafting: Auto-grafting, Homo-grafting and Hetero-grafting. Rootstock aged one year and resulted by two chosen genetic types, namely, SnobarJablah and Alhafa were used. Scions, they were taken either from seedlings with age of one year resulted by these two types or from branches aged one year from the selected two types as well. Grafting was conducted by using Whip Graft way in spring. Auto-grafting has indicated the importance and the role of biological and genetic factors for grafts and their impact on rates of grafting success. Concerning rates of success, the results have shown that Auto-grafting surpassed Hetero-grafting with a significant reference for both of two genetic types, regardless if the used scion was young or old.In addition, Auto-grafting has shown surpass on other kinds of grafting, in terms of subsequent growth of scions. On the other hand, a variety in biological indicators values has been noticed between the two genetic studied types. In favour of SnobarJablahtype againstAlhafaʼs type. However, the differences of values were not significant for the most of conducted measures.As for the age of scions, the results have pointed out that values of Hetero-grafting with young scions surpassed values of Hetero-grafting with old scions in terms of the rate of grafting success and values of biological studied indicators.